Presence of autoantibodies against HeLa small nuclear ribonucleoproteins in chagasic and non-chagasic cardiac patients - Bosetto, M.C. [UNESP]; Peixoto, M.S. [UNESP]; Castro, L.I.R. de [UNESP]; Cicarelli, R.M.B. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2004)
We detected anti-human small nuclear ribonucleoprotein (snRNP) autoantibodies in chagasic patients by different immunological methods using HeLa snRNPs. ELISA with Trypanosoma cruzi total lysate antigen or HeLa human U small nuclear ribonucleoproteins (UsnRNPs) followed by incubation with sera from chronic chagasic and non-chagasic cardiac patients was used to screen and compare serum reactivity. Western blot analysis using a T. cruzi total cell extract was also performed in order to select some sera for Western blot and immunoprecipitation assays with HeLa nuclear extract. ELISA showed that 73 and 95% of chronic chagasic sera reacted with HeLa UsnRNPs and T. cruzi antigens, respectively. The Western blot assay demonstrated that non-chagasic cardiac sera reacted with high molecular weight proteins present in T. cruzi total extract, probably explaining the 31% reactivity found by ELISA. However, these sera reacted weakly with HeLa UsnRNPs, in contrast to the chagasic sera, which showed autoantibodies with human Sm (from Stefanie Smith, the first patient in whom this activity was identified) proteins (B/B', D1, D2, D3, E, F, and G UsnRNP). Immunoprecipitation reactions using HeLa nuclear extracts confirmed the reactivity of chagasic sera and human UsnRNA/RNPs, while the other sera reacted weakly only with U1snRNP. These findings agree with previously reported data, thus supporting the idea of the presence of autoimmune antibodies in chagasic patients. Interestingly, non-chagasic cardiac sera also showed reactivity with T. cruzi antigen and HeLa UsnRNPs, which suggests that individuals with heart disease of unknown etiology may develop autoimmune antibodies at any time. The detection of UsnRNP autoantibodies in chagasic patients might contribute to our understanding of how they develop upon initial T. cruzi infection.
Keywords: Chagas' disease; Autoantibodies; Small nuclear ribonucleoprotein; Trypanosoma cruzi; HeLa cells; Cross-reactivity